Up-regulation of expression and lack of 5' CpG island hypermethylation of p16 INK4a in HPV-positive cervical carcinomas - Frank Georgy A; Andreeva Yulia Y; Katargin Alexey N; Volgareva Galina M; Zavalishina Larisa E; Golovina Daria A; Ivanova Tatiana A; Kisseljov Fjodor L; Kisseljova Natalia P (BMC Cancer, 2007)
Abstract Background High risk type human papilloma viruses (HR-HPV) induce carcinomas of the uterine cervix by expressing viral oncogenes E6 and E7. Oncogene E7 of HR-HPV disrupts the pRb/E2F interaction, which negatively regulates the S phase entry. Expression of tumor suppressor p16ink4a drastically increases in majority of HR-HPV associated carcinomas due to removal of pRb repression. The p16ink4a overexpression is an indicator of an aberrant expression of viral oncogenes and may serve as a marker for early diagnostic of cervical cancer. On the other hand, in 25–57% of cervical carcinomas hypermethylation of the p16 INK4a promoter has been demonstrated using a methylation-specific PCR, MSP. To evaluate a potential usage of the p16 INK4a 5' CpG island hypermethylation as an indicator of tumor cell along with p16ink4a overexpression, we analyzed the methylation status of p16 INK4a in cervical carcinomas Methods Methylation status of p16 INK4a was analyzed by MSP and by bisulfite-modified DNA sequencing. The expression of p16ink4a was analyzed by RT-PCR and by immunohistochemical technique. Results The extensive methylation within p16 INK4a 5' CpG island was not detected either in 13 primary cervical carcinomas or in 5 cancer cell lines by bisulfite-modified DNA sequencing (including those that were positive by MSP in our hands). The number and distribution of rare partially methylated CpG sites did not differ considerably in tumors and adjacent normal tissues. The levels of the p16 INK4a mRNA were increased in carcinomas compared to the normal tissues independently of the number of partially methylated CpGs within 5'CpG island. The transcriptional activation of p16 INK4a was accompanied by p16ink4a cytoplasmic immunoreactivity in the majority of tumor cells and presence of a varied number of the p16 positive nuclei in different tumors. Conclusion Hypermethylaion of the p16INK4a 5' CpG island is not a frequent event in HR-HPV-positive cervical carcinomas and cannot be an effective marker of cancer cells with up-regulated expression of p16ink4a. Our data confirm other previous studies claiming specific p16INK4a up-regulation in the majority of cervical carcinomas at both the protein and mRNA levels. Cytoplasmic accumulation of p16ink4a is a feature of cervical carcinomas.